UNEMPLOYMENT RATE IN UZBEKISTAN AND OPPORTUNITIES TO REDUCE IT - Meyliyev O.R. (Scholar Express Journals, 2023)
The article presents the level of unemployment in the Republic of Uzbekistan, its impact on economic development, the level of unemployment among young people and also a theoretical and practical analysis of its negative aspects. In the process of modernization of the economy, practical recommendations are given for solving and improving the problems related to ensuring employment in the country
Keywords: Unemployment; level of unemployment; types of unemployment